2019
DOI: 10.1097/brs.0000000000002813
|View full text |Cite
|
Sign up to set email alerts
|

Measurement Techniques and Utility of Hounsfield Unit Values for Assessment of Bone Quality Prior to Spinal Instrumentation

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
110
0
14

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(124 citation statements)
references
References 18 publications
0
110
0
14
Order By: Relevance
“…26,27 However, many authors have advocated that CT HU values can serve as a potential proxy to DXA given the moderate correlation between HU values and osteoporosis. 5,7,9,10,28 Another reason that HUs on preoperative CT are valuable as opposed to DXA is that it can be readily measured on the PACS, a system that nearly all modern medical centers use. For instance, in our study, 93 of 138 patients who underwent single-level LLIF had preoperative CT scans, but only 12 of 138 patients had a DXA scan before surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26,27 However, many authors have advocated that CT HU values can serve as a potential proxy to DXA given the moderate correlation between HU values and osteoporosis. 5,7,9,10,28 Another reason that HUs on preoperative CT are valuable as opposed to DXA is that it can be readily measured on the PACS, a system that nearly all modern medical centers use. For instance, in our study, 93 of 138 patients who underwent single-level LLIF had preoperative CT scans, but only 12 of 138 patients had a DXA scan before surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Zaidi et al have shown correlation between HU values and success of lumbar fusions. 28 Mi et al showed that in patients undergoing transforaminal lumbar interbody fusion with unilateral pedicle screw fixation, lower HU values were significantly associated with subsidence (113.4 vs 127.9 HUs, p < 0.05). 4 To our knowledge, there is very limited literature published about HUs and subsidence in LLIF.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al (16) recommended that radiologists examine and report osteoporosis on routine abdominal CT. In addition, Zaidi et al (17)noted that HU value measurement is a useful and practical technique for assessing bone quality that could be reported by a radiologist in all patients with preexisting abdominal CT scans. Pickhardt et al (18), in their comprehensive series using CT and DXA, determined that their threshold values for osteoporosis at vertebrae L1 to T12 ranged from 110 to 120 HU, whereas normal vertebral density was determined as 200 HU or higher.…”
Section: Discussionmentioning
confidence: 99%
“…36 However, previous studies have focused on the lumbar spine, establishing thresholds of 135 HU for osteopenic spines, 120 HU for the risk of pedicle screw loosening, 110 HU for osteoporotic spines, and 90 HU for the risk of vertebral body fracture. 32,37,38 Although these numbers may be useful in identifying osteoporosis in patients undergoing spinal surgery for degenerative pathology, the same correlation has not been clearly shown in patients undergoing ASD correction, especially at the UIV in the thoracic spine. 39 Thus, in ASD patients, the HUs of the LT spine may be more critical than the HUs of the lumbar spine.…”
Section: Discussionmentioning
confidence: 99%